Fast high-resolution late gadolinium enhancement magnetic resonance imaging for an accurate detection of myocardial radiofrequency catheter ablation lesions. (19th May 2022) - Sridi, S; Stuber, M; Jais, P; Cochet, H; Bustin, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Whole- heart high-resolution free-breathing late gadolinium enhancement (HR-LGE) is a key sequence for detecting radiofrequency catheter ablation (RFCA) lesions. However, long acquisition time is the main limitation especially for dyspneic and claustrophobic patients. Purpose: We aimed to introduce an accelerated HR-LGE technique for the detection of myocardial RFCA lesions. Method: An under sampled (3-fold) navigator-gated whole- heart HR-LGE (acquired resolution of 1.25 mm3) sequence combined with advanced patch-based low-rank reconstruction was implemented on a 1.5 CMR scanner. Three sheep prospectively underwent radiofrequency ablation at multiple endocardial and epicardial sites. The animals were imaged 3 months later using conventional post-contrast LGE (PSIR, voxel size 1.8x1.4x6mm) and the proposed sequence. A reader graded image quality and diagnostic value of both LGE imaging. Results: The acceleration allowed for acquisition times of 3 min 22s ± 20 s at 1.25 mm resolution. Compared with 2D PSIR, HR-LGE showed comparable image quality (P= 0.03). All LGE- positive segments on 2D PSIR in LV myocardium were also detected on HR-LGE (6 segments). Two additional enhanced segments were only visible on HR-LGE (8 segments). LGE-positive segments in RV myocardium were detected on HR-LGE (4 segments) while 2D PSIR was either definitely negative (2 segments) or uncertain (2 segments). Conclusion: Accelerated whole-heart HR- LGE allows an accurate detection of left and right myocardial RFCA lesions.